LANGUAGE ECOLOGY AS LINGUISTIC THEORY - Mark Garner (Universitas Muhammadiyah Surakarta, 2005)
language ecology was proposed by Einar Haugen in 1972 as the study of the interaction of any given language and its environment. Despite some use of the term in the literature, sociolinguistics have failed to develop the potenstial that Haugen saw in an ecological approach. Recent developments in ecological thought, however; when applied to language, raise questions about many basic assumptions of conventional linguistics. For example, from an ecological perspective, language is not a rule-governed system, but a form of patterned behaviour arising from the needs of human socialtity: communication, culture, and community. As Haugen foresaw, language ecology offers an exciting alternative approach to linguistic theory.Key words: language ecology, patterned behaviour, holistic, dynamic, and interactive